Kemampuan Pemecahan Masalah Matematika Peserta Didik dengan Pendekatan Onto-Semiotic Ditinjau Dari Gender - Junidhar, Lailya Mifta (AKSIOMA : Jurnal Sains Ekonomi dan Edukasi, 2024)
Mathematics is one of the important sciences for every human being. In mathematics there is problem solving listed in the goals of mathematics. So that students are required to have the ability to solve mathematical problems. To analyze students' problem-solving abilities, an approach that discusses procedures for solving mathematical problems is needed, one of which is the onto-semiotic approach. The onto-semiotic approach is a relevant approach to be used in analyzing students' mathematical problems solving abilities. In problems solving it is known that each student has their own ability, especially in gender differences. Therefore, this study aims to analyze students' mathematical problems solving abilities with an onto-semiotic approach in terms of gender. This study used a descriptive method with a qualitative approach and the instruments used to collect data were test questions and interviews. Data analysis techniques used include data reduction, data presentation, and drawing conclusions. Checking the validity of the data is done by using the triangulation method. The conclusion of this study shows that students with male and female gender are able to fulfill the indicators in the onto-semiotic approach by relatively the same way of thinking.